Reconsidering the Foundations of the Concept of Reflection of R. Descartes and I. Kant in the Transcendental Phenomenology of E. Husserl - Milerius, Nerijus (Problemos, 1996)
The paper deals with the analysis of the genesis of transcendental reflection in the works of R. Descartes, I. Kant, and E. Husserl. The problems of subject-object, immanence-transcendence, essence-existence, objectivation, identity of gnoseological subject, i.e., those which emerge in the articulation of the modern reflection theory, are discussed as well. The paper reveals the inevitable limits of pure reflection. Descartes and Kant restricted reflection by ontological presuppositions. Only such restrictions make possible true knowledge and the intersubjective sphere. E. Husserl reduces these presuppositions but does not prove the possibility of the intersubjective sphere in a phenomenologically consistent way.